Modern And Simple Society Education In Dealing With Socio-Cultural Changes, Modernization And development - Muhammad Rifai; Kasful Anwar US; As'ad Isma (International Journal of Education, Vocational and Social Science, 2023)
Factors that cause socio-cultural changes are: Increase or decrease in population, changes in geographical environment, movement to new environments, contact with people of different cultures, natural and social issues, the birth or death of a leader, inventions/innovations. There are also several factors that impede change, for example the lack of intensive communication with other communities; slow science and technology development; very traditional nature of society ; there are interests that are firmly entrenched in society; negative prejudice against new things; fear of shakiness in society when changes occur; ideological barriers ; and the influence of custom or custom. The relationship between developed and developing countries. The necessity of developing education will open the door to the modern world, because only with education can socio-cultural changes be carried out, namely the development of knowledge, adjustment of values and attitudes that support development and mastery of various skills in using advanced technology to accelerate the process development. The theory of socio-cultural value orientation in this theory says that in society it can be seen where the orientation of values emphasizes a future-oriented view of time, a view of nature that emphasizes that natural laws can be known and mastered, a view that work is something that can give rise to more work, the view that all human beings are equal, are all value orientations that have led to progress